Recommendations for evaluating the safety of medicinal products containing nanoparticles - R. N. Alyautdin; B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Recommendations for preclinical safety assessment of medicinal products containing nanoparticles are presented. The recommendations provide conditions for research acute and chronic toxicity of nanotherapeutics, methods for their quantitative and qualitative assessments.